Management of Bonsai intoxication at emergency service: A review of 61 cases - Karabulut, Nadiye; Demirel Dengi, Seda; Görükmez, Sündüs; Arıca, Seçil; Yeniocak, Selman (Journal of Surgery and Medicine, 2018)
Aim: The aim of this study was to determine the effects of bonzai by assessing the correlation between the clinical and laboratory findings of cases diagnosed with bonsai intoxication who had been monitored in the emergency service. Methods: This study was approved by ‘’Haseki Training and Research Hospital Ethical Committee of Non-Pharmacological Studies’’ with approval number of:183 on 28.01.2015. A retrospective evaluation was performed on 61 bonsai intoxication cases who had been monitored and treated in the emergency service. The clinical findings of the pre- and post-treatment and laboratory findings of each case were evaluated. Results: According to the initial clinical assessment of bonsai intoxication cases who were admitted to the emergency service, the Glasgow coma score (GCS) was found as 8 (E2, V2, M4), 9 (E2, V2, M5) and 4 (E1, V1, M2) in 87% (n=53), 10% (n=6) and 3.2% (n=2), respectively. The pupil reflex was fixed and dilated in 90% (n=52); whereas, it was normal in 10% (n=9). Although, the biochemical parameters (78.9%, n=49) and blood gas levels (98.6%, n=60) were within the normal physiological range in accordance with their age and gender, the elevated serum levels of creatine kinase (CK) and creatine kinase myocardial band (CK-MB) was determined in 21% of the cases (n=12). The pH value of venous blood gas of a case, in whom the elevated levels of CK-MB and CK were found to be directly proportional, was determined as 7.16. The level of troponin-I, electrocardiogram (ECG) findings, hemogram and coagulation parameters were also within the normal physiological range in accordance with their age and gender. The mean venous blood glucose levels were found as 120 ± 29 mg/dL (min: 78 mg/dL, max: 214 mg/dL), and a reverse correlation was detected between the hyperglysemic conditions of the cases and GCS scores on arrival. Of the bonsai intoxication cases, 60 had been treated with hydration therapy (0.9% NaCl solution, 15cc/min, 2000 cc), one was intubated by using midazolam, and monitored and treated in the emergency service. Conclusion: Patients with different states of consciousness have been frequently encountered in the emergency service. This condition may depend on various factors such as alcohol, certain endocrine diseases (hypo-hyperglycemia, thyrotoxicosis, etc.), trauma, infections (central nervous system infections, sepsis, etc.), cerebrovascular disorders and intoxication. By considering the elevated synthetic cannabinoid (SC) abuse among the adolescents recently, the use of CB should be kept in mind for the pre-diagnosis of the juvenile patients who were brought to the emergency service with loss of consciousness.